DEPRESSION AND SMUGGLING PROHIBITED AMONG PRISONERS - Sugumaran Sukanderam; Saralah Devi (Polteknik Ilmu Pemasyarakatan, 2022)
Tainted research information on depression and smuggling prohibited articles among prisoners has garnered researchers’ attention to answer unanswered questions. This study aims to reveal about relationship between depression and smuggling prohibited articles into the prison. By using Beck Depression Inventory (BDI) measurement as to elicit the pertinent information from 66 prisoners. The results show three hypotheses are insignificant, yet, it will be useful to prison management to focus on reducing depression level among prisoners which are being triggered by other factors.